High-energy few-cycle pulses: post-compression techniques - Nagy, Tamas; Simon, Peter; Veisz, Laszlo (Advances in physics: X, 2021)
Contemporary ultrafast science requires reliable sources of high-energy few-cycle light pulses. Currently two methods are capable of generating such pulses: post compression of short laser pulses and optical parametric chirped-pulse amplification (OPCPA). Here we give a comprehensive overview on the post-compression technology based on optical Kerr-effect or ionization, with particular emphasis on energy and power scaling. Relevant types of post compression techniques are discussed including free propagation in bulk materials, multiple-plate continuum generation, multi-pass cells, filaments, photonic-crystal fibers, hollow-core fibers and self-compression techniques. We provide a short theoretical overview of the physics as well as an in-depth description of existing experimental realizations of post compression, especially those that can provide few-cycle pulse duration with mJ-scale pulse energy. The achieved experimental performances of these methods are compared in terms of important figures of merit such as pulse energy, pulse duration, peak power and average power. We give some perspectives at the end to emphasize the expected future trends of this technology.